Analisis Pengaruh Motivasi Belajar Ekstrinsik Dalam Pembelajaran Daring Terhadap Mutu Hasil Belajar Di AMIK Bina Sriwijaya Palembang - Leni Maimuna (Jurnal Penjaminan Mutu, 2021)
The goal of this research was to determine the effect of extrinsic learning motivation (learning motivation that comes from lecturers in online lectures) on Discrete Mathematics quality of learning outcomes. Data was collected from 30 lecture students in Informatics Management Faculty of AMIK Bina Sriwijaya Palembang, who takeÂ Discrete Mathematics as their subject, by using a random sampling method. The measured variables are extrinsic learning motivation and discrete mathematics quality of learning outcomes. Simple regression analysis is used in testing the effect of extrinsic learning motivation on Discrete Mathematics quality of learning outcomes. The results of the research using 30 respondents showed that the correlation coefficient of 0.449, which means the corelation between the two variables in the medium category and the coefficient of determination 0.201 which means that lecture students quality of learning outcomes are influenced by extrinsic learning motivation (learning motivation originating from lecturers in online lectures) by 20.1%. Based on data analysis, the regression coefficient is positive (+) so it can be concluded that the increasing extrinsic learning motivation (learning motivation originating from lecturers in online lectures) will affect the increase in lecture students quality of learning outcomes.